The International and Political Journal: The time scoop for the term of the Iraqi parliament under the permanent constitution of Iraq of 2005 - Ameen, Assistant prof Dr. Iqbal Abdullah (The International and Political Journal, 2024)
Iraq has adopted a parliamentary representative system of government, and one of the most prominent features of this system is the necessity of having three authorities in the state that work alongside some and under the weight of all circumstances and times, which are the legislative, executive and judicial authority, and that each of these authorities is independent in performing its work with cooperation and balance between the authorities According to the democratic system, those powers reach power through elections by the people, especially the legislative authority that exercises power in the name of the people and on their behalf, and to prevent the tyranny of that authority that represents the people, it does not continue in power permanently, but the constitution has specified a specific period for it to exercise Its tasks are under the supervision of its authority, and it is elected by the people. After the end of the period specified for the legislative authority to perform its duties, the choice is left to the people to re-elect them when their performance is distinguished, or others are elected upon failure to perform their duties and in this research we will know whether the term of the parliament’s term is sufficient to perform its work and what are the cases that terminate the parliament’s work before The end of its specified term, or the extension of the council’s work.